The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1977
DOI: 10.1177/00220345770560102901
|View full text |Cite
|
Sign up to set email alerts
|

Association Between HLA-Antigens and Periodontal Disease

Abstract: Patients with periodontitis juvenilis and patients with periodontitis were tissue typed. In the juvenile group, frequencies of tissue type specificities HLA-A9, HLA-A28, and HLA-BW15 were significantly increased as compared to the findings in the general population. In the periodontitis groups, no significant tissue type deviations were found.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
38
1
2

Year Published

1985
1985
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 69 publications
(43 citation statements)
references
References 3 publications
2
38
1
2
Order By: Relevance
“…Most recently, Shapira and colleagues (1994) found that, among non-Ashkenazi lews, HLA antigens A9 and Bl 5 are associated with the generalized form of early-onset periodontal disease but not with the localized form. Earlier studies in other populations also reported an association between HLA-A9 and early-onset periodontal disease (Reinholdt et al, 1977;MarggrafeUl., 1983;KloudaeU/., 1986;AmereUl., 1988); the criteria for case selection suggest that primarily generalized early-onset periodontal disease cases were included in these studies . Shapira and colleagues (1994) conclude that generalized earlyonset periodontal disease and localized early-onset disease are different diseases "under different genetic control".…”
Section: Population Association Studiesmentioning
confidence: 86%
“…Most recently, Shapira and colleagues (1994) found that, among non-Ashkenazi lews, HLA antigens A9 and Bl 5 are associated with the generalized form of early-onset periodontal disease but not with the localized form. Earlier studies in other populations also reported an association between HLA-A9 and early-onset periodontal disease (Reinholdt et al, 1977;MarggrafeUl., 1983;KloudaeU/., 1986;AmereUl., 1988); the criteria for case selection suggest that primarily generalized early-onset periodontal disease cases were included in these studies . Shapira and colleagues (1994) conclude that generalized earlyonset periodontal disease and localized early-onset disease are different diseases "under different genetic control".…”
Section: Population Association Studiesmentioning
confidence: 86%
“…Since activation of lymphocyte and -blast transformation is controlled by the HLA system in man, association between the HLA system and various diseases, including localized juvenile periodontitis, has been sought. For example, juvenile periodontitis patients have been found to have decreased frequency of HLA-A2 (Kaslick et al, 1975;Kaslick et al, 1980), and increased frequency of HLA-A9, HLA-A28, and HLA-BW15 (Reinholdt et al, 1977). However, Cullinan et al (1980) and Saxen and Koskimies (1984) did not confirm these alterations in HLA frequency.…”
mentioning
confidence: 96%
“…(1977) had reported a positive association of HLA-A9, A28 and B25 with AP. [22] Klouda et al . (1986) reported a higher frequency of HLA-A9 and HLA-A24 in English Caucasians with AP.…”
Section: Discussionmentioning
confidence: 99%